Novel oncolytic vaccinia virus armed with interleukin-27 is a potential therapeutic agent for the treatment of murine pancreatic cancer - Bing Han; Yong Yang; Zhe Zhang; Pengju Wang; Yaohe Wang; Louisa S Chard Dunmall; Lihong Wang; Lijuan Chen; Ruimin Wang; Yanru Wang; Yangyang Jia; Guanghao Zhao; et al. (Journal for ImmunoTherapy of Cancer)
Background Pancreatic cancer has a complex immunosuppressive tumor microenvironment (TME), which is highly resistant to conventional therapies and emerging cancer immunotherapies. Oncolytic viruses are multifaceted killers of malignant tumors, which can selectively infect, replicate in and lyse tumor cells, release tumor-associated antigens to stimulate specific antitumor immune responses, and recruit immune cells into the TME, turning “cold” tumors “hot”. Here, we report a novel vaccinia virus (VV), VVLΔTKΔN1LΔA41L (with deletion of thymidine kinase (TK), N1L, and A41L genes) armed with interleukin 27 (IL-27), that can cure established tumors and promote long-term antitumor immunity in murine pancreatic cancer tumor models.Methods A novel oncolytic VV with deletion of the TK, N1L, and A41L genes, and expression of the red fluorescent protein (RFP) gene (VVL-TD-RFP) was constructed using CRISPR-Cas9-based homologous recombination. This virus was armed with IL-27, creating VVL-TD-IL-27. The characteristics of these viruses were evaluated in vitro using viral replication assays, cytotoxicity assays and ELISA. The antitumor effects of VVL-TD-IL-27 were evaluated using a variety of pancreatic cancer tumor models in vivo, and the mechanisms of antitumor effects were explored using flow cytometry, immunohistochemistry, ELISA and quantitative PCR.Results VVL-TD-RFP cured 71.4% of tumor-bearing mice, compared with 14.3% of animals treated with VVLΔTKΔN1L that does not have an A41L gene deletion. Efficacy was mainly dependent on elevated dendritic cell (DC) populations, activation of DC, CD86+ DC, and CD8+ effector memory T cells in the TME. Efficacy was further enhanced by arming VVL-TD-RFP with IL-27, which resulted in a cure rate of 100% and promoted long-term antitumor immunity. VVL-TD-IL-27 treatment increased the proportion of CD8+ TEM and decreased the proportion of regulatory T cells and macrophages in tumor tissues. It also polarized macrophages to an M1 phenotype in vivo. Furthermore, IL-27 exhibits strong anti-angiogenic effects.Conclusions VVL-TD-mIL-27 is a potential immunotherapy agent for the treatment of pancreatic cancer, and a clinical study of this virus is warranted.